Miocamycin‐Containing Triple Therapy for H. pylori Infection. Issue 4 (11th March 2013) - Dore, Maria Pina; Massidda, Marco; Yilmaz, Ozlem; Demiray‐Gürbüz, Ebru; Manca, Alessandra; Bassotti, Gabrio
Abstract Introduction In Northern Sardinia, one‐week triple standard therapies containing a proton‐pump inhibitor and two antibiotics for H. pylori infection have an average cure rate of 57% largely due to a high prevalence of antimicrobial resistance. The efficacy of miocamycin‐containing treatment for 10 days was evaluated. Materials and Methods Patients referred to the endoscopy service for dyspeptic symptoms were enrolled. H. pylori infection was defined as a positive rapid urease test, presence of the bacteria on gastric biopsies, and a positive 13C‐UBT. Treatment consisted of 10 days with omeprazole 20 mg, miocamycin water‐soluble 900 mg, and tinidazole 500 mg all bid. Success was evaluated 40–50 days after the end of therapy and defined by a negative 13C‐UBT. Compliance was considered good if at least 90% of the total number of the pills were taken. Fluorescent in situ hybridization (FISH) technique was applied on paraffin‐embedded gastric tissue sections to test susceptibility to clarithromycin of the bacteria. Results 50 patients were enrolled (mean age; 52, 36% men). Miocamycin‐containing therapy cured 86% (42/49; 95% CI = 72–94%) of infected patients by PP analysis. Susceptibility data (FISH) was available for 38 patients. Cure rates for the 28 with clarithromycin‐susceptible infection was 96% vs 50% for those with resistant or mixed infection, (p = .003). Good compliance was recorded in 48 patients. None of the patients discontinued therapy. Conclusions Miocamycin appears to be a valid alternative for clarithromycin for H. pylori eradication. Head‐to‐head studies will be needed to ascertain whether it is superior.